Electrochemical Impedance Evaluation Of Coating Under Simulated Splash Zone Condition - SHAHROL AZRAI, FARID AIMAN (IRC, 2020)
One of the requirement for a high performance coating to be applied to an offshore structure is to conduct and withstand long term accelerated weathering test for 4200 hours. However, in some cases, the offshore structure’s coating may be experiencing premature failure, even though it meets the acceptance criteria of the lab test. Hence, the aim of this paper is to study the quantitative test method by introducing electrochemical impedance test into the accelerated weathering test, and characterize the progressive stages of coating physical degradation under simulated splash zone condition. The test cycle consist of 72 hours of UV-condensation, followed by 96 hours of salt fog exposure. Each cycle, bode plot and Nyquist plot was obtained when running electrochemical impedance test, and were used for validation of the coating’s performance.